Analisis Perbandingan Persepsi Konsumen Mengenai Store Atmosphere Pada Ritel Modern Dan Ritel Konvensional (Studi Kasus Pada Indomaret Dan Toko Dedy Di Tenggarong) - Novianti, Silvia Nurma; Luthman, Awang Yacoub; Ilham, Ilham (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2018)
Abstract:Our highly perceived form of word is the distance that reads these small traders fret. If retail business grows year by year in the absence of prevailing regulations then it is with conventional market which will also reduce revenue from the conventional market itself, because the adjacent distance is certainly cheaper than traditional market. The purpose of this research is to know and analyze comparison of consumer perception about store atmosphere in modern retail (Indomaret) and conventional retail (Toko Dedy). The data used is primary data. This research method using purposive sampling, with the terms and conditions applicable. Samples studied were 91 respondents. Number of variables studied is 1 ie store atmosphere with 4 indicators. In this research using Paired Sample T-Test analysis by comparing the average value in modern retail (Indomaret) and conventional retail (Toko Dedy). From the results of the study stated that the first hypothesis statement in this study which states